KONSEP ISLAM RAHMATAN LIL ‘ALAMIN SEBAGAI LANDASAN ETIKA EKOLOGIS DALAM KRISIS LINGKUNGAN MODERN - Sahdan, Fahrizal; Sa'idy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The global environmental crisis demonstrates that purely technical and economic approaches have not been sufficient to address increasingly complex ecological damage. Environmental issues are not only related to the exploitation of natural resources but are also influenced by a moral and spiritual crisis in humanity’s perception of nature. This study aims to analyze the concept of rahmatan lil ‘alamin as the foundation of Islamic ecological ethics in addressing the modern environmental crisis. This study employs a qualitative method based on literature review, utilizing a thematic exegesis approach and interpretive analysis of Quranic verses, hadiths, classical and contemporary exegetical works, as well as literature on environmental ethics and sustainability. The results indicate that the concept of rahmatan lil ‘alamin embodies universal values that position humanity as stewards responsible for maintaining ecological balance, rather than as entities free to exploit the environment. The principles of amanah (trust), mizan (balance), tawazun (harmony), along with prohibitions against israf (wastefulness) and fasad (corruption), form the framework of Islamic ecological ethics that aligns with the principles of sustainability and intergenerational justice. This study also found that the modern environmental crisis is a consequence of an anthropocentric paradigm and consumptive behavior that disregards spiritual values and ethical considerations toward nature. Therefore, the revitalization of the concept of “rahmatan lil ‘alamin” is essential as an ecological paradigm that integrates spiritual, moral, social, and environmental dimensions in fostering sustainability awareness.